A real-world retrospective study to determine the safety and effectiveness of naftifine 2% cream in the treatment of Tinea cruris and Tinea corporis in Indian patients - Soni, Anil; Tripathi, Aditya; Sarkar, Soumajyoti; Sarkar, Dibyajyoti; Shinde, Rajendra; Makwana, Alka; Jaiswal, Ashok; Chinda, Monika (International Journal of Research in Dermatology, 2025)
Background: This real-world retrospective analysis of the case record forms (CRFs) was done to evaluate the safety, effectiveness, compliance, and tolerability of naftifine 2% cream in treating superficial infections, especially Tinea corporis and Tinea cruris, in Indian patients. Methods: The data was collected from 158 dermatologists/physicians’ outpatient department in India, on using naftifine 2% cream in patients presenting with new or recurrent Tinea infections. The CRFs of 1258 patients who had previously visited the dermatology outpatient department from July 2023 to May 2024 and received naftifine 2% cream as monotherapy or in combination therapy at the discretion of the treating physician were included in the study. Results: A total of 1,258 eligible CRFs were analyzed, revealing that 81% of patients treated with naftifine 2% cream achieved clinical cure, while 99.6% achieved mycological cure. Adverse events were reported in only 2.6% (n=33) of patients, and naftifine 2% cream treatment was well tolerated. Conclusions: This retrospective study suggests that naftifine 2% cream is safe and effective in patients with superficial fungal infections, including Tinea corporis and Tinea cruris.